KAJIAN POTENSI PENGEMBANGAN TANAMAN MARKISA KUNING (PASSIFLORA FLAVICARVA) PADA TANAH ALFISOL - SARDIANA, I KETUT; RATNA ADI, I G.P. (Agrotrop : Journal on Agriculture Science; Vol 1 No 2 (2011), 2012)
Potential Study of Yellow Maracujá (Passiflora flavicarva) Suitability on Alfisol Soil The objectives of this study was to determine land characteristics and land suitability for maracujá (Passiflora flavicarva) on Alfisols soil in District of Melaya, Jembrana Regency. The study used the land unit with homogeneus on climate, terrain, and landuse as sampling units. The climate data was analysed by classifying the rainfall degree based on Oldeman and Schmidt-Ferguson system.The characteristics of land were fixed based on the field survey and the soil analysis in the laboratory. Class or sub class of land suitability is based on matching system between land qualities and crop requirements. The results show that land suitability for maracujá (Passiflora flavicarva) commodities is categorized as moderately suitable (S2) with two limiting factors i.e. C-organic and total nitrogen of the soils. Corganic in the soils is needed to keep the balance of the elements and humidity of the soils. The cultivation of this plant, needed at least 74 kilograms organic matter/plant/year.
Keywords: land suitability evaluation, dragon fruits, alfisols soils